Pharmaceutical chemistry. Section 2.1. Analysis of medicines that affect the central nervous system: study and methodical guide for 4th year students of the specialty "Pharmacy, Industrial Pharmacy" - Shabelnik, K. P.; Derevianko, N. V.; Borsuk, S. O.; Шабельник, Костянтин Петрович; Дерев'янко, Наталя Вікторівна; Борсук, Сергій Олександрович (Запорізький державний медико-фармацевтичний університет, 2024)
The study guide for students is compiled in accordance with the re-quirements of the Central Methodical Council of Zaporizhzhia State Med-ical and Pharmaceutical University. Published for the first time.